Induction of photoautotrophy in Chlorophytum borivilianum Sant. et Fernand, regenerated in vitro - Jha, Aparajita; Bansal, Yogendra Kumar (Journal of Phytology, 2012)
The potential for photoautotrophic growth was studied in in vitro cultures of Chlorophytum borivilianum Sant. et Fernand. Best in vitro shoot differentiation was observed on MS medium supplemented with BAP 5 mg L-1, whereas MS + IBA 2 mg L-1 produced maximum root number and root length. The regenerated plantlets were then sequentially transferred to liquid basal medium having a gradual decrease in sucrose concentration [3%, 2%, 1.5%, 1%, 0.5% and 0%] after 48 hours stay in each. The plantlets thus formed were successfully hardened and transferred to sand-soil and farmyard manure mixture [1:1:1]. Approx. 90% of C. borivilianum regenerants survived after successful hardening.